Post-synthetically modified porous covalent framework (PCF) for high proton conduction - Samanta, Partha; Desai, Aamod; Anothumakkool, Bihag; Shirolkar, Mandar; Karmakar, Avishek; Kurungot, Sreekumar; Ghosh, Sujit (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Porous Covalent Framework; Post-synthetic Modification; proton conduction

Coherent fusion of water array and protonated amine in a metal-sulfate-based coordination polymer for proton conduction - Manna, Biplab; Anothumakkool, Bihag; Desai, Aamod V.; Samanta, Partha; Kurungot, Sreekumar; Ghosh, Sujit K. (Inorganic Chemistry, 2015)
A new function of metal-sulfate-based co-ordination polymer (CP) for proton,conduction Was investigated through rational integration of a continuous water array and protonated amine in the coordination space of the CP. The H-bonded arrays of watet molecules along with nitrogen-rich aromatic cation (protonated melamine) facilitate proton conduction in the compound under humid conditions. Although several reports of metal-oxalate/phosphate-based CPs showing proton conduction are known, this is the first designed synthesis of a metal sulfate-based CP bearing-Water arrays functioning as a solid-state proton conductor:

Hydrogen-bonded organic frameworks (HOFs): a new class of porous crystalline proton-conducting materials - Karmakar, Avishek; Illathvalappil, Rajith; Anothumakkool, Bihag; Sen, Arunabha; Samanta, Partha; Desai, Aamod V.; Kurungot, Sreekumar; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2016)
Two porous hydrogen-bonded organic frameworks (HOFs) based on arene sulfonates and guanidinium ions are reported. As a result of the presence of ionic backbones appended with protonic source, the compounds exhibit ultra-high proton conduction values (sigma) 0.75x 10(-2)Scm(-1) and 1.8x10(-2)Scm(-1) under humidified conditions. Also, they have very low activation energy values and the highest proton conductivity at ambient conditions (low humidity and at moderate temperature) among porous crystalline materials, such as metal-organic frameworks (MOFs) and covalent organic frameworks (COFs). These values are not only comparable to the conventionally used proton exchange membranes, such as Nafion used in fuel cell technologies, but is also the highest value reported in organic-based porous architectures. Notably, this report inaugurates the usage of crystalline hydrogen-bonded porous organic frameworks as solid-state proton conducting materials.
Keywords: guanidinium; hydrogen-bonded organic frameworks; porous crystalline frameworks; proton conduction; sulfonates

Enhanced proton conduction by post-synthetic covalent modification in a porous covalent framework - Samanta, Partha; Desai, Aamod V.; Anothumakkool, Bihag; Shirolkar, Mandar M.; Karmakar, Avishek; Kurungot, Sreekumar; Ghosh, Sujit K. (Journal of Materials Chemistry A, 2017)
A highly chemically stable porous covalent framework (PCF-1) based on ether linkages has been synthesized, which exhibits no loss up to similar to 500 degrees C along with retention of integrity under acidic, basic and oxidative reagent conditions. Owing to its thermal and chemical stability, post-synthetic covalent modification was executed for the introduction of pendant sulphonic acid (-SO3H) groups. The covalently modified compound (PCF-1-SO3H) presents a remarkably high conductivity (ca. 0.026 S cm(-1)), with an similar to 130 fold enhancement in proton conductivity over the parent compound. This value is comparable with those of commercially used Nafion-based proton conducting materials and stands as the highest known value in the regime of post-synthetically modified porous organic frameworks. It is noteworthy to mention that PCF-1 is stable in both acidic and alkaline media, which is not commonly observed for most of the porous materials trialed as proton conducting materials, including metal organic frameworks.